Innovative Design of Solar Benches for Public Spaces: Renewable Energy with Arduino Integration - Kango, Riklan; Pongtularan, Ezra Hartarto; Ain, Mohamad Isram M. (Journal La Multiapp, 2023)
This research aims to design and implement an innovative park bench that combines solar panel technology with the Arduino platform. The methodology of this research consists of designing the integration of solar panels with Arduino components that are assembled integrated on the physical bench. In the analysis phase, measurements of solar energy production were conducted under various light and weather conditions. The performance of the system in battery charging and fulfillment of energy needs was evaluated. Environmental data from Arduino sensors were analyzed to illustrate the effect of environmental conditions on system operation. The results showed that the solar bench produced higher energy during daytime and reduced during nighttime conditions. The system can supply energy for purposes such as lighting and charging electronic devices. The voltage and current data at night show inefficiency in charging the solar panel, while the cell phone charger condition works as long as the battery is above 15%. In addition, environmental analysis through Arduino sensors revealed a correlation between light intensity and energy production and usage. These findings can be used to optimize the operation of the smart bench system based on changing environmental conditions. In conclusion, this solar bench design has the potential to reduce environmental impacts and support the use of renewable energy in urban public spaces, with the potential to increase public awareness of sustainable energy